Night and Day: Diel Differences in Ship Strike Risk for Fin Whales (Balaenoptera physalus) in the California Current System - Keen, Eric M.; Scales, Kylie L.; Rone, Brenda K.; Hazen, Elliott L.; Falcone, Erin A.; Schorr, Gregory S. (Frontiers in Marine Science, 2019)
Collisions with ships (ship strikes) are a pressing conservation concern for fin whales (Balaenoptera physalus) along western North America. Fin whales exhibit strong diel patterns in dive behavior, remaining near the surface for most of the night, but how this behavior affects ship-strike risk is unknown. We combined diel patterns of surface use, habitat suitability predictions, and ship traffic data to evaluate spatial and temporal trends in ship-strike risk to fin whales of the California Current System (CCS). We tested a range of surface-use scenarios and found that both increased use of the upper water column and increased ship traffic contribute to elevated ship-strike risk at night. Lengthening nights elevate risk during winter throughout the CCS, though the Southern California Bight experienced consistently high risk both day and night year-round. Within designated shipping lanes, total annual nighttime strike risk was twice daytime risk. Avoidance probability models based on ship speed were used to compare the potential efficacy of speed restrictions at various scales. Speed reductions within lanes may be an efficient remediation, but they would address only a small fraction (13%) of overall ship-strike risk. Additional speed restrictions in the approaches to lanes would more effectively reduce overall risk.